2021
DOI: 10.4414/smw.2021.20477
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus routine EEG in critically ill adults: reimbursement analysis of a randomised trial

Abstract: BACKGROUND: Continuous EEG (cEEG) is increasingly used in critically ill patients, but it is more resource-intensive than routine EEG (rEEG). In the US, cEEG generates increased hospitalisation charges. This study analysed hospital-related reimbursement for participants in a Swiss multicentre randomised controlled trial that assessed the relationship of cEEG versus repeated rEEG with outcome. METHODS:We used data of the CERTA study (NCT03129438), including demographics, clinical variables and reimbursement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Further analysis of the CERTA dataset shed an interesting and partly new light regarding the role of cEEG versus rEEG in ICU patients, beyond the aforementioned outcomes. Of relevance, in a diagnosis-related group reimbursement system (which is common to many European countries, but also beyond) cEEG does not significantly generate more costs [ 68 ], unlike in the USA [ 5 ], and thus does not represent any financial incentive. Considering prognostic EEG features, cEEG allows, in comparison to rEEG, a significant increased detection not only of ictal events but also of generalized rhythmic delta [ 69 ] and sleep spindles [ 70 ], which are both related to favorable prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of the CERTA dataset shed an interesting and partly new light regarding the role of cEEG versus rEEG in ICU patients, beyond the aforementioned outcomes. Of relevance, in a diagnosis-related group reimbursement system (which is common to many European countries, but also beyond) cEEG does not significantly generate more costs [ 68 ], unlike in the USA [ 5 ], and thus does not represent any financial incentive. Considering prognostic EEG features, cEEG allows, in comparison to rEEG, a significant increased detection not only of ictal events but also of generalized rhythmic delta [ 69 ] and sleep spindles [ 70 ], which are both related to favorable prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous EEG (cEEG) monitoring is paramount in critically ill patients, offering superior sensitivity over routine or intermittent EEG, which typically entails brief recordings lasting 20–40 min [ 53 55 ]. Studies suggest that while brief EEG can be cost-effective and comparable in seizure detection rates as cEEG in certain contexts like post-cardiac arrest patients [ 56 , 57 ], the prolonged duration of cEEG generally yields better prognostic accuracy for clinical outcome.…”
Section: Continuous Eeg For Seizure and Status Epilepticus Detectionmentioning
confidence: 99%
“…13,14 Indeed, it has been demonstrated that cEEG proves more sensitive for seizure or SE detection than routine EEG (rEEG, typically lasting 20-30 minutes). 15,16 On the other hand, it is more time-, resource-and person-consuming, 11,[15][16][17] which may lead to questioning the costeffectiveness in some settings. 18 Therefore, large-scale cEEG implementation in many centers outside North America is still somewhat limited.…”
Section: Introductionmentioning
confidence: 99%